Experimental flow conditions effects on a bottom-mounted ducted twin vertical axis tidal turbine compared to real sea conditions (Proceedings of the European Wave and Tidal Energy Conference, 2023)
From 2019 to 2021, HydroQuest tested its 1 MW-rated ducted twin vertical axis tidal turbine (2-VATT) at Paimpol-Bréhat test site, France. At this site, the turbulent intensity is evaluated about 15 % and extreme wave conditions up to 6 m significant wave height with 12 s peak period were observed during the two years of demonstration. In addition, the current vertical velocity profile is sheared with about 20 % velocity difference between the top and the bottom of the turbine, and the average directions of the ebb and flood tides are about 22° asymmetrical. The bottom mounted 2-VATT was instrumented for performance and loads assessment which allowed the certification of the power curve, both in flood and ebb tides, as well as the analysis of the sea state influence on the turbine behaviour. Based on that experience, the company wants to gain confidence in its design process by comparing those results to numerical and lab-scale experiments ones.Along the past three years, an important amount of work has been achieved to widely characterise the behaviour of the 1/20 scale 2-VATT similar to the 1MW-rated demonstrator. The turbine was tested in many different operating conditions in the Ifremer’s wave and current flume tank to try to reproduce full-scale conditions and turbine response. Those conditions include a wide range of operating points and incident velocities, facing aligned and misaligned currents, with and without vertical velocity shear, with and without bathymetry generated turbulence, with and without surface waves following and against the current. In this presentation, we propose to synthesise the effects of all these conditions on the 2-VATT response to highlight the most critical ones in the design process of such a device, in comparison to the results obtained at sea.To this date, we showed that the lab-scale model behaviour differs between ebb and flood tide current conditions due to the difference of relative counter-rotation of the two columns of rotors and to the base asymmetry. The wake is also significantly different as it recovers 30 % faster in the flood tide configuration compared to the ebb. We also found that the presence of a sheared and misaligned incident current barely affects the ducted 2-VATT average performance. However, it modifies the torque repartition between the rotors leading to an increase of the power fluctuations. Furthermore, when adding bathymetry obstacle upstream, the high flow shear and turbulence also generate strong power fluctuations on the 2-VATT. The load fluctuations are significantly increased, impacting the structure fatigue compared to a flat floor configuration, but the risks of device drifting or toppling are not affected. The waves impact the power and loads fluctuations too while barely affecting the average performance; and the average performance increases with the Reynolds number in the tank. Those two latter points still need investigations to better characterise their effect on the 2-VATT.